Effects of Hepatic Impairment on the Pharmacokinetics of Abrocitinib and Its Metabolites. (17th April 2021) - Wang, Ellen Q.; Le, Vu; O'Gorman, Melissa; Tripathy, Sakambari; Dowty, Martin E.; Wang, Lisy; Malhotra, Bimal K.
Abstract: Abrocitinib, an oral once‐daily Janus kinase 1 selective inhibitor, is under development for treatment of atopic dermatitis. This phase 1, nonrandomized, open‐label, single‐dose study (NCT03626415) investigated the effect of hepatic impairment on pharmacokinetics (PK), safety, and tolerability of abrocitinib and its metabolites after a 200‐mg oral dose. Twenty‐four subjects with varying degrees of hepatic function (normal, mild, and moderate impairment) were enrolled (N = 8/group). Active moiety PK parameters were calculated as the sum of unbound PK parameters for abrocitinib and its active metabolites. For abrocitinib, the ratios (percentages) of adjusted geometric means for area under the concentration‐time curve from time 0 extrapolated to infinite time (AUCinf ) and maximum plasma concentration (Cmax ) were 133.33 (90% confidence interval [CI], 86.17‐206.28) and 94.40 (90%CI, 62.96‐141.55), respectively, for subjects with mild hepatic impairment vs normal hepatic function. The corresponding comparisons of ratios (percentages) for AUCinf and Cmax were 153.99 (90%CI, 99.52‐238.25) and 105.53 (90%CI, 70.38‐158.24), respectively, for subjects with moderate hepatic impairment. Exposures of the metabolites were generally lower in subjects with hepatic impairment. For abrocitinib active moiety, the ratios (percentages) of adjusted geometric means of unbound AUCinf were 95.74 (90%CI, 72.71‐126.08) and 114.82 (90%CI, 87.19‐151.20) in subjects with mild and moderate impairment vs normal hepatic function, respectively. Abrocitinib was generally safe and well tolerated. Hepatic impairment had no clinically relevant effect on the PK and safety of abrocitinib and the exposure of abrocitinib active moiety. These results support the use of abrocitinib without dose adjustment in subjects with mild or moderate hepatic impairment.